Carbon Dioxide Laser Microsurgical Median Glossotomy for Resection of Lingual Dermoid Cysts - Corvers, Kristien; Hens, Greet; Meulemans, Jeroen; Delaere, Pierre; Hermans, Robert; Vander Poorten, Vincent (Frontiers in Surgery, 2016)
Dermoid cysts are epithelial-lined cavities with skin adnexae in the capsule. Only 7% present in the head and neck. Between 2004 and 2013, 4 patients with a lingual dermoid cyst underwent a microsurgical carbon dioxide (CO²) laser resection via a median sagittal glossotomy approach. This approach is an elegant technique combining superior visualization, hemostasis, and little postoperative edema with good wound healing, allowing for perfect function preservation of the tongue.